POTENTIAL OF FARNESOL AS A MAO-A INHIBITOR CANDIDATE FOR THERAPY OF MENTAL HEALTH DISORDERS: AN IN SILICO STUDY - Hafidz Ardan Kaizar; Yennie Agnes Pranata (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2026)
Mental health disorders, particularly depression, remain a global problem with a high prevalence among university students. Conventional therapy using chemical antidepressants is often limited by side effects, delayed onset of action, and limited effectiveness. Farnesol, a sesquiterpene found in essential oils, has been reported to exhibit biological activity in the central nervous system. This study aims to explore the potential of farnesol as a candidate Monoamine Oxidase-A (MAO-A) inhibitor through an in silico approach. Docking studies were performed on 5HT1A, 5HT2A, GABA, and MAO-A receptors using SwissDock, with the ligand prepared from the PubChem database. Binding interactions were visualized using ChimeraX and LigPlot, while toxicity evaluation was analyzed using SwissADME and ADMETlab 2.0. The results showed that farnesol had the best binding energy toward the MAO-A receptor (-8.43 kcal/mol) compared with the control compound phenelzine (-6.62 kcal/mol). Farnesol also showed good blood-brain barrier penetration ability and a low toxicity profile. Therefore, farnesol has the potential to be developed as a natural antidepressant candidate derived from essential oils. Further in vitro and in vivo studies are required to verify these findings.